QUARTER LIFE CRISIS (QLC): KAJIAN PSIKOLINGUISTIK PADA ALBUM LAGU HINDIA MENARI DENGAN BAYANGAN - Hasanah, Dina Fitria; Mulyati, Yeti; Hadianto, Daris (Sunan Kalijaga State Islamic University Yogyakarta, 2023)
The issue of mental health has been in the spotlight in this decade, and various media have voiced and given their perspectives, including a singer, Hindia, in the song lyrics of their album Menari dengan Bayangan. The songs specifically portray mental health problems that impact persons in their 20s who are experiencing a quarter-life crisis. In order to examine the truth of this hypothesis, a content analysis research method was chosen which was studied using psycholinguistic theory. Dissected 12 songs and 3 skits from people closest to Hindia which are included in the album entitled Menari dengan Bayangan. The results of the study show,1) the album contains the four stages of quarter life crisis, 2) the lyrics of the songs on the album Menari dengan Bayangan define a quarter-life crisis from the lowest to the last stage that can exceed the crisis in early adulthood, and 3) listeners to songs in the album Menari dengan Bayangan responded positively to every lyric contained in it and helped them to get out of the mental crisis they were facing.